FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Shrubs and Degraded Permafrost Pave the Way for Tree Establishment in Subarctic Peatlands - Juul Limpens; Thijs P. M. Fijen; Iris Keizer; Johan Meijer; Fanny Olsthoorn; Ana Pereira; Roel Postma; Mariette Suyker; Harri Vasander; Milena Holmgren (Ecosystems, 2021)
Arctic and subarctic ecosystems are changing rapidly in species composition and functioning as they warm twice as fast as the global average. It has been suggested that tree-less boreal landscapes may shift abruptly to tree-dominated states as climate warms. Yet, we insufficiently understand the conditions and mechanisms underlying tree establishment in the subarctic and arctic regions to anticipate how climate change may further affect ecosystem structure and functioning. We conducted a field experiment to assess the role of permafrost presence, micro-topography and shrub canopy on tree establishment in almost tree-less subarctic peatlands of northern Finland. We introduced seeds and seedlings of four tree-line species and monitored seedling survival and environmental conditions for six growing seasons. Our results show that once seedlings have emerged, the absence of permafrost can enhance early tree seedling survival, but shrub cover is the most important driver of subsequent tree seedling survival in subarctic peatlands. Tree seedling survival was twice as high under an intact shrub canopy than in open conditions after shrub canopy removal. Under unclipped control conditions, seedling survival was positively associated with dense shrub canopies for half of the tree species studied. These strong positive interactions between shrubs and trees may facilitate the transition from today’s treeless subarctic landscapes towards tree-dominated states. Our results suggest that climate warming may accelerate this vegetation shift as permafrost is lost, and shrubs further expand across the subarctic.

Imaging the role of blood–brain barrier disruption in normal cognitive ageing - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
To investigate whether blood–brain barrier (BBB) disruption is a potential mechanism of usual age-related cognitive decline, we conducted dynamic contrast–enhanced (DCE) MRI to measure BBB leakage in a healthy sample, and investigated the association with longitudinal cognitive decline. In a sample of neurologically and cognitively healthy, older individuals, BBB leakage rate in the white and grey matter and hippocampus was measured using DCE MRI with pharmacokinetic modelling. Regression analysis was performed to investigate whether the leakage rate was associated with decline in cognitive performance (memory encoding, memory retrieval, executive functioning and processing speed) over 12 years. White and grey matter BBB leakages were significantly associated with decline in memory retrieval. No significant relations were found between hippocampal BBB leakage and cognitive performance. BBB disruption already being associated with usual cognitive ageing, supports that this neurovascular alteration is a possible explanation for the cognitive decline inherent to the ageing process. More insight into BBB leakage during the normal ageing process could improve estimation and interpretation of leakage rate in pathological conditions. The current results might also stimulate the search for strategies to maintain BBB integrity and help increase the proportion people experiencing successful ageing. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Increase in blood–brain barrier leakage in healthy, older adults - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Ed H. B. M. Gronenschild; Walter M. Palm; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
Blood–brain barrier (BBB) breakdown can disrupt nutrient supply and waste removal, which affects neuronal functioning. Currently, dynamic contrast-enhanced (DCE) MRI is the preferred in-vivo method to quantify BBB leakage. Dedicated DCE MRI studies in normal aging individuals are lacking, which could hamper value estimation and interpretation of leakage rate in pathological conditions. Therefore, we applied DCE MRI to investigate the association between BBB disruption and age in a healthy sample. Fifty-seven cognitively and neurologically healthy, middle-aged to older participants (mean age: 66 years, range: 47–91 years) underwent MRI, including DCE MRI with intravenous injection of a gadolinium-based contrast agent. Pharmacokinetic modeling was applied to contrast concentration time-curves to estimate BBB leakage rate in each voxel. Subsequently, leakage rate was calculated in the white and gray matter, and primary (basic sensory and motor functions), secondary (association areas), and tertiary (higher-order cognition) brain regions. A difference in vulnerability to deterioration was expected between these regions, with especially tertiary regions being affected by age. Higher BBB leakage rate was significantly associated with older age in the white and gray matter, and also in tertiary, but not in primary or secondary brain regions. Even in healthy individuals, BBB disruption was stronger in older persons, which suggests BBB disruption is a normal physiologically aging phenomenon. Age-related increase in BBB disruption occurred especially in brain regions most vulnerable to age-related deterioration, which may indicate that BBB disruption is an underlying mechanism of normal age-related decline. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Forgetting the new locations of one’s keys: spatial-memory interference in Korsakoff’s amnesia - Albert Postma; Sascha G. Morel; Margot E. Slot; Erik Oudman; Roy P. C. Kessels (Experimental Brain Research, 2018)

Solubility Constraints on Aquatic Ecotoxicity Testing of Anionic Surfactants - J. Hammer; A. M. Tukker; J. F. Postma; J. J. -H. Haftka; J. L. M. Hermens; P. de Voogt; M. H. S. Kraak (Bulletin of Environmental Contamination and Toxicology, 2018)

Biorefinery of the macroalgae Ulva lactuca: extraction of proteins and carbohydrates by mild disintegration - P. R. Postma; O. Cerezo-Chinarro; R. J. Akkerman; G. Olivieri; R. H. Wijffels; W. A. Brandenburg; M. H. M. Eppink (Journal of Applied Phycology, 2018)

Influence of Sewered Versus Septic Systems on Watershed Exports of E. coli - G. Iverson; C. P. Humphrey; M. H. Postma; M. A. O’Driscoll; A. K. Manda; A. Finley (Water, Air, & Soil Pollution, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

First confirmed record of a leucistic Antarctic fur seal pup born outside the Scotia Arc Islands - M. Wege; M. Postma; C. A. Tosh; P. J. N. de Bruyn; M. N. Bester (Polar Biology, 2015)

Objective allergy markers and risk of cancer mortality and hospitalization in a large population-based cohort - Niloofar Taghizadeh; Judith M. Vonk; Jeannette J. Hospers; Dirkje S. Postma; Elisabeth G. E. de Vries; Jan P. Schouten; H. Marike Boezen (Cancer Causes & Control, 2015)

Age-related reproductive variation in a wild marine mammal population - Martin Postma; Marthán N. Bester; P. J. Nico de Bruyn (Polar Biology, 2013)

The role of Streptococcus pneumoniae in community-acquired pneumonia among adults in Europe: a meta-analysis - M. H. Rozenbaum; P. Pechlivanoglou; T. S. Werf; J. R. Lo-Ten-Foe; M. J. Postma; E. Hak (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Phenotypic variability and modelling of root structure of wild Lupinus angustifolius genotypes - Ying Long Chen; Vanessa M. Dunbabin; Johannes A. Postma; Art J. Diggle; Jairo A. Palta; Jonathan P. Lynch; Kadambot H. M. Siddique; Zed Rengel (Plant and Soil, 2011)

Spared unconscious influences of spatial memory in diencephalic amnesia - Albert Postma; Rémy Antonides; Arie J. Wester; Roy P. C. Kessels (Experimental Brain Research, 2008)

Individual variation in human spatial ability: differences between men and women in object location memory - Maartje de Goede; Roy P. C. Kessels; Albert Postma (Cognitive Processing, 2006)

The effect of neuronal morphology and membrane-permeant weak acid and base on the dissipation of depolarization-induced pH gradients in snail neurons - A. Pantazis; P. Keegan; M. Postma; C. J. Schwiening (Pflügers Archiv - European Journal of Physiology, 2006)

Effect of above‐ground plant species on soil microbial community structure and its impact on suppression of Rhizoctonia solani AG3 - P. Garbeva; J. Postma; J. A. Van Veen; J. D. Van Elsas (Environmental Microbiology, 2006)
Summary The extent of soil microbial diversity is seen to be critical to the maintenance of soil health and quality. Different agricultural practices are able to affect soil microbial diversity and thus the level of suppressiveness of plant diseases. In a 4‐year field experiment, we investigated the microbial diversity of soil under different agricultural regimes. We studied permanent grassland, grassland turned into arable land, long‐term arable land and arable land turned into grassland. The diversity of microbial communities was described by using cultivation‐based and cultivation‐independent methods. Both types of methods revealed differences in the diversities of soil microbial communities between different treatments. The treatments with higher above‐ground biodiversity generally maintained higher levels of microbial diversity. Moreover, a positive correlation between suppression of Rhizoctonia solani AG3 and microbial diversity was observed. Permanent (species‐rich) grassland and grassland turned into maize stimulated higher microbial diversities and higher levels of suppressiveness of R. solani AG3 compared with the long‐term arable land. Effects of agricultural practices on Bacillus and Pseudomonas communities were also observed and clear correlations between the levels of suppressiveness and the diversities of these bacterial groups were found. This study highlighted the importance of agricultural management regime for soil microbial community structure and diversity as well as the level of soil suppressiveness.

DISSOLVING STOCK DISCRETENESS WITH SATELLITE TRACKING: BOWHEAD WHALES IN BAFFIN BAY - M. P. Heide‐JØrgensen; K. L. Laidre; M. V. Jensen; L. Dueck; L. D. Postma (Marine Mammal Science, 2006)
Nine bowhead whales ( Balaena mysticetus ) were instrumented with satellite transmitters in West Greenland in May 2002 and 2003. Transmitters were either encased in steel cans or imbedded in floats attached to wires. Transmitters mounted in steel cans had a high initial failure rate, yet those that were successful provided tracking durations up to seven months. Float tags had a low initial failure rate and initially provided large numbers of positions; however, they had deployment durations of only 2–33 d. All tracked whales departed from West Greenland and headed northwest towards Lancaster Sound in the end of May. Three tags with long tracking durations (197–217 d) recorded movements of whales (1 ♂, 2 ♀) into December in 2002 and 2003. All of these individuals remained within the Canadian High Arctic or along the east coast of Baffin Island in summer and early fall. By the end of October, all three whales moved rapidly south along the east coast of Baffin Island and entered Hudson Strait, an apparent wintering ground for the population. One of the whales did not visit Isabella Bay on east Baffin Island, the locality used for abundance estimation from photographic reidentification of individuals. The movements of whales tagged in this study raise critical questions about the assumed stock discreteness of bowhead whales in Foxe Basin, Hudson Strait, and Davis Strait and indicate current estimates of abundance are negatively biased.

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Frontal-Lobe Involvement in Spatial Memory: Evidence from PET, fMRI, and Lesion Studies - Roy P. C. Kessels; Albert Postma; Elze M. Wijnalda; Edward H. F. de Haan (Neuropsychology Review, 2000)

Characterization of the KNOX class homeobox genes Oskn2 and Oskn3 identified in a collection of cDNA libraries covering the early stages of rice embryogenesis - A. Dorien Postma-Haarsma; Ira I.G.S. Verwoert; Oscar P. Stronk; Jan Koster; Gerda E.M. Lamers; J. Harry C. Hoge; Annemarie H. Meijer (Plant Molecular Biology, 1999)

Control and regulation of metabolic fluxes in microbes by substrates and enzymes - K. van Dam; N. Jansen; P. Postma; P. Richard; G. Ruijter; M. Rutgers; H. P. Smits; B. Teusink; J. van der Vlag; M. Walsh; H. V. Westerhoff (Antonie van Leeuwenhoek, 1993)

Energetics of glucose uptake in a Salmonella typhimurium mutant containing uncoupled enzyme IIGlc - G. J. G. Ruijter; P. W. Postma; K. van Dam (Archives of Microbiology, 1991)

Quantitative aspects of glucose metabolism by Escherichia coli B/r, grown in the presence of pyrroloquinoline quinone - R. W. J. Hommes; J. A. Simons; J. L. Snoep; P. W. Postma; D. W. Tempest; O. M. Neijssel (Antonie van Leeuwenhoek, 1991)

The influence of the culture pH value on the direct glucose oxidative pathway in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

The separate roles of PQQ and apo-enzyme syntheses in the regulation of glucose dehydrogenase activity in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. T. D. Herman; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

Energetics of glucose uptake in Salmonella typhimurium - M. Driessen; P. W. Postma; K. van Dam (Archives of Microbiology, 1987)

The functional significance of glucose dehydrogenase in Klebsiella aerogenes - R. W. J. Hommes; B. van Hell; P. W. Postma; O. M. Neijssel; D. W. Tempest (Archives of Microbiology, 1985)

Virulence ofEscherichia coli strains isolated from urine of patients with acute cystitis and from faeces of healthy women - J. F. van den Bosch; P. Postma; D. van Brenk; P. A. M. Guinée; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1981)

Regulation of sugar transport in Salmonella typhimurium - P. W. Postma; B. J. Scholte (Antonie van Leeuwenhoek, 1981)

Virulence of Escherichia coli in acute pyelonephritis, acute cystitis and asymptomatic bacteriuria - J. F. van den Bosch; P. L. Oe; P. Postma; J. de Graaff; D. M. MacLaren; W. H. Jansen; P. A. M. Guinée (Antonie van Leeuwenhoek, 1980)

Hemolysis and urinary virulence of Escherichia coli. - J. F. Bosch; P. Postma; J. Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1980)

Urinary virulence of E. coli in experimental haematogenous pyelonephritis - J. F. van den Bosch; P. Postma; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1979)